A new cryptic species distinguished from Ischnochiton comptus (Gould, 1859) (Polyplacophora: Ischnochitonidae) in central Honshu, Japan. (1st October 2016) - Owada, Masato
ABSTRACT: Ischnochiton boninensis Bergenhayn, 1933 and Ischnochiton comptus (Gould, 1859) are commonly found in central Honshu, Japan. These species are frequently misidentified because of the striking similarity in their overall appearance, and with the slight differences requiring microscopic examination. The present study investigated these distinctions, and I . comptus is further divided into a cryptic pair of species on the basis of morphological and genetic analyses. Genetic analyses revealed that I . comptus and its new cryptic sister species are separated by a relatively large pairwise genetic distance, similar to the distance between either of these and I . boninensis . Morphological observations indicated that only I . boninensis has clear granulation of the central areas of the intermediate valves, and the other two species, including I . comptus, are more similar in their radulae and girdle scales. Despite these similarities, specimens originally identified as I . comptus can be divided into separate species based on molecular and differences in the sculpture of the central area of the intermediate valves. One of these is here described as a new cryptic species distinct from I . comptus .